All About High Plus and High Minus Spherical Lens and Aspheric Lens - Chowdhury, Partha Haradhan; Shah, Brinda Haren; Tiwari, Nripesh (International Journal For Research In Health Sciences And Nursing, 2020)
This paper describes about Plus lens Spherical Design, Minus lens spherical design and Aspheric lens designs.